2023
DOI: 10.1038/s41598-023-36811-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning to automatically evaluate HER2 gene amplification status from fluorescence in situ hybridization images

Abstract: Human epidermal growth factor receptor 2 (HER2) gene amplification helps identify breast cancer patients who may respond to targeted anti-HER2 therapy. This study aims to develop an automated method for quantifying HER2 fluorescence in situ hybridization (FISH) signals and improve the working efficiency of pathologists. An Aitrox artificial intelligence (AI) model based on deep learning was constructed, and a comparison between the AI model and traditional manual counting was performed. In total, 918 FISH imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…The purpose of this step is to learn, through training, how to map global information to another space in order to obtain the parameters needed for calculating attention weights. The sigmoid activation function is mainly useful in mapping the input to an output in the range (0, 1) as shown in Formula (10).…”
Section: Seam Attention Modulementioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this step is to learn, through training, how to map global information to another space in order to obtain the parameters needed for calculating attention weights. The sigmoid activation function is mainly useful in mapping the input to an output in the range (0, 1) as shown in Formula (10).…”
Section: Seam Attention Modulementioning
confidence: 99%
“…In recent years, the integration of medical imaging and computer science has become increasingly close. Medical image detection methods using deep learning have become a popular research topic [6][7][8][9][10][11]. However, medical image data are often large and complicated, and there are only limited labeled data available, which increases the difficulty of training deep learning models.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated the potential of an AI-powered HER2 analyzer to mitigate interobserver variability and aid pathologists in achieving a consistent evaluation of HER2 expression levels [ 125 ]. Furthermore, several studies have used AI models to predict the amplification state of HER2 by analyzing digitized fluorescence ISH (FISH) images [ 126 127 128 ].…”
Section: Predictive or Prognostic Factors For Breast Cancermentioning
confidence: 99%